Pengaruh Tepung Cangkang Rajungan (Portunus pelagicus) dalam Ransum terhadap Kadar Kolesterol Serum dan Pertambahan Bobot Badan Tikus Putih (Rattus norvegicus) - I U Warsono; M Fattah W; A Parakkasi (Media Peternakan, 2004)
Crab shells contain the highest percentage of chitin. Chitin and its derivatives have many properties that make them attractive for a wide variety of applications. This study was conducted to determine the effect of crab (Portunus pelagicus) shells as a source of chitin in ration on serum cholesterol and weight gain of rats (Rattus norvegicus). The study was carried out in a factorial experiment 2 x 5 with 3 replications. The first factor is sex and the second factor is crab shells of 5 levels i.e., 0%, 5%, 10%, 15%, and 20% in ration. The study showed that there were no interaction effect between sex and crab shells levels in diet on all parameters. Serum cholesterol levels decreased (P > 0.05) and weigh gain increased (P < 0.01) when crab shells were included in the diets. The highest reduction of serum cholesterol level (14,8%) was observed at crab shells level of 10%, but the highest weight gain was reached at 5% inclusion of crab shells. These results suggest that crab shells in rat diets reduced serum cholesterol level and increased weight gain. Key words: crab shells, cholesterol, gain, rat